2023
DOI: 10.1002/iid3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Serum C‐reactive protein greater than 75 mg/dL as an early available laboratory predictor of severe COVID‐19: A systematic review

Pershang Nazemi,
SeyedAhmad SeyedAlinaghi,
Ayein Azarnoush
et al.

Abstract: IntroductionSevere COVID‐19 management is still challenging. Having a laboratory factor to predict the severity of a patient's condition can be very useful in how to approach each patient. There have been studies concentrating on the correlation between serum C‐reactive protein (CRP) level and COVID‐19 severity but we aim to reach a threshold for CRP in disease severity determination.MethodsWe conducted a thorough search on PubMed, Web of Science and Google Scholar databases from early 2019 to October 2021, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…During acute inflammatory responses to COVID-19, there is usually a rapid and significant increase in serum CRP levels. Elevated CRP fluctuation during hospitalization has been identified as the primary cause of ICU admission with a poor prognosis ( 41 ). Analysis revealed that critical patients have higher CRP levels, indicating a more significant inflammatory response than non-critical patients ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…During acute inflammatory responses to COVID-19, there is usually a rapid and significant increase in serum CRP levels. Elevated CRP fluctuation during hospitalization has been identified as the primary cause of ICU admission with a poor prognosis ( 41 ). Analysis revealed that critical patients have higher CRP levels, indicating a more significant inflammatory response than non-critical patients ( 13 ).…”
Section: Discussionmentioning
confidence: 99%